Structural changes in multilayer systems containing InxGa₁₋xAs₁₋yNy quantum wells - Fodchuk, I.M.; Gevyk, V.B.; Gimchinsky, O.G.; Kislovskii, E.N.; Kroytor, O.P.; Molodkin, V.B.; Olihovskii, S.I.; Pavelescu, E.M.; Pessa, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The investigations of multilayer nano-scale systems contained one or two quantum wells are carried out by double-crystal X-ray diffractometry. Processes of interdiffusion of In, Ga atoms and their influence on properties of such systems are considered. The content of nitrogen in quantum wells and buffer layers are defined. It is determined that InxGa₁₋xAs₁₋yNy system has perfect crystalline structure, and interface between layers is coherent.